2014
DOI: 10.1002/2014jc009906
|View full text |Cite
|
Sign up to set email alerts
|

Estimating satellite salinity errors for assimilation of Aquarius and SMOS data into climate models

Abstract: Constraining dynamical systems with new information from ocean measurements, including observations of sea surface salinity (SSS) from Aquarius and SMOS, requires careful consideration of data errors that are used to determine the importance of constraints in the optimization. Here such errors are derived by comparing satellite SSS observations from Aquarius and SMOS with ocean model output and in situ data. The associated data error variance maps have a complex spatial pattern, ranging from less than 0.05 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
(21 reference statements)
2
24
0
Order By: Relevance
“…The availability of satellite sea‐surface salinity (SSS) data since the launch of the European Space Agency's (ESA's) Soil Moisture and Ocean Salinity (SMOS) mission in 2009, and subsequent launches of the National Aeronautics and Space Administration's (NASA's) Aquarius and Soil Moisture Active Passive (SMAP) missions in 2011 and 2015 respectively, has allowed various efforts to use the data for validation of ocean forecasts (e.g. Vinogradova et al, ; Martin, ). Efforts to assimilate the satellite SSS data have also taken place.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of satellite sea‐surface salinity (SSS) data since the launch of the European Space Agency's (ESA's) Soil Moisture and Ocean Salinity (SMOS) mission in 2009, and subsequent launches of the National Aeronautics and Space Administration's (NASA's) Aquarius and Soil Moisture Active Passive (SMAP) missions in 2011 and 2015 respectively, has allowed various efforts to use the data for validation of ocean forecasts (e.g. Vinogradova et al, ; Martin, ). Efforts to assimilate the satellite SSS data have also taken place.…”
Section: Introductionmentioning
confidence: 99%
“…For examples, the data have been used to study tropical instability waves [Lee et al, 2012Yin et al, 2014], SSS associated with river plumes and marginal seas [e.g., Grodsky et al, 2012;Gierach et al, 2013;Zeng et al, 2014;Fournier et al, 2016], intraseasonal SSS variations associated with the Madden-Julian Oscillation [Grunseich et al, 2013;Guan et al, 2014;Li et al, 2015], mesoscale eddies [e.g., Reul et al, 2014b], Rossby waves [Menezes et al, 2014], and interannual variations associated with climate modes [e.g., Qu and Yu, 2014;Du and Zhang, 2015]. The data have also been used to improve ocean state estimation and seasonal climate prediction [e.g., Köhl et al, 2014;Vinogradova et al, 2014;Toyoda et al, 2015;Hackert et al, 2014]. SSS is being retrieved from NASA's Soil Moisture Active Passive (SMAP) to provide continuity of NASA's SSS measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Grunseich, Subrahmanyam, and Wang (2013) showed that Aquarius-based SSS can detect the propagation of Madden-Julian oscillation. SSS from the SMOS and Aquarius missions also showed a positive impact on an ocean general circulation model simulation (Chakraborty et al 2014;Vinogradova et al 2014).…”
Section: Introductionmentioning
confidence: 96%